Antioxidants improve vascular function in children conceived by assisted reproductive technologies: A randomized double-blind placebo-controlled trial. (29th August 2020) - Rimoldi, Stefano F; Sartori, Claudio; Rexhaj, Emrush; Bailey, Damian M; Marchi, Stefano F de; McEneny, Jane; Arx, Robert von; Cerny, David; Duplain, Hervé; Germond, Marc; Allemann, Yves; Scherrer, Urs
Abstract: Aims: Children conceived by assisted reproductive technology (ART) display vascular dysfunction. Its underlying mechanism, potential reversibility and long-term consequences for cardiovascular risk are unknown. In mice, ART induces arterial hypertension and shortens the life span. These problems are related to decreased vascular endothelial nitric oxide synthase (eNOS) expression and nitric oxide (NO) synthesis. The aim of this study was to determine whether ART-induced vascular dysfunction in humans is related to a similar mechanism and potentially reversible. To this end we tested whether antioxidants improve endothelial function by scavenging free radicals and increasing NO bioavailability. Methods and results: In this prospective double-blind placebo controlled study in 21 ART and 21 control children we assessed the effects of a four-week oral supplementation with antioxidant vitamins C (1 g) and E (400 IU) or placebo (allocation ratio 2:1) on flow-mediated vasodilation (FMD) of the brachial artery and pulmonary artery pressure (echocardiography) during high-altitude exposure (3454 m), a manoeuver known to facilitate the detection of pulmonary vascular dysfunction and to decrease NO bioavailability by stimulating oxidative stress. Antioxidant supplementation significantly increased plasma NO measured by ozone-based chemiluminescence (from 21.7 ± 7.9 to 26.9 ± 7.6 µM, p = 0.04) and FMD (from 7.0 ± 2.1 to 8.7 ± 2.0%, p = 0.004) and attenuated altitude-induced pulmonary hypertension (from 33 ± 8 to 28 ± 6 mm Hg, p = 0.028) in ART children, whereas it had no detectable effect in control children. Conclusions: Antioxidant administration to ART children improved NO bioavailability and vascular responsiveness in the systemic and pulmonary circulation. Collectively, these findings indicate that in young individuals ART-induced vascular dysfunction is subject to redox regulation and reversible.